Inquiry-based learning in Bangladesh: insights into middle and high school students’ experiences and 21st century skill development - Lizoon Nahar; Crystal Machado (Disciplinary and Interdisciplinary Science Education Research)
Abstract Educators worldwide are using a variety of approaches to develop students’ 21st century skills, better known as the 4Cs: communication, collaboration, critical thinking, and creativity. As part of a larger QUAN-QUAL mixed method study, this paper describes urban Bangladeshi students, teachers, and site coordinators’ thoughts about the influence of a six-month inquiry-based learning (IBL) science project on middle and high students’ 4C skill development. We analyzed survey data from 109 students and 20 teachers, interview data from site coordinators, and Zoom transcripts to identify areas of growth. Students reported that the project fostered the development of communication and collaboration skills. We also noted gains in critical thinking and creativity skills. Nonparametric statistics confirmed that grade levels have a statistically significant effect on the 4C skills development. However, curriculum type (British vs. National) did not have a considerable influence, showing that teachers can use IBL projects to develop 4C skills regardless of curriculum variations. This study highlights the benefits of providing teachers with professional development that targets design and implementation of IBL to foster 4C skills development across content areas and educational settings.